SYNERGISTIC EFFECT OF CADMIUM IN COMBINATION WITH UVB RADIATIONS IN PS II PHOTOCHEMISTRY OF THE CYANOBACTERIUM SPIRULINA PLATENSIS - D. GUNA SEKHAR (The Bioscan, 2011)
In this present investigation an attempt has been made to study the synergistic effect of UV-B radiation (2-6Wm2 ) in combination with cadmium chloride (0.2-0.6mM) on photosystem II catalyzed electron transport in cyanobacterium Spirulina platensis. UV-B radiation alone caused 52% inhibition at 4 Wm-2. Similarly when cadmium is applied 61% loss in the Hill reaction was noticed at 0.6 mM concentration. When both the stresses are applied in combination there was 84% loss in the PS II catalyzed electron transport .The reason for the loss of PS II catalyzed electron transport could be due to alterations at water oxidation complex .Thus when cadmium treated cells are exposed to UV-B the effect on PS II photochemistry is additive in the cyanobacterium Spirulina platensis.